DINAMIKA LPTK MENUJU PERGURUAN TINGGI KELAS DUNIA (WORLD CLASS UNIVERSITY/WCU) - Agus Santosa, Iskandar Agung (Perspektif Ilmu Pendidikan, 2017)
LPTK as a producer of educators must be proactive towards a world-class higher education (world class university / WCU). The study was conducted in 2014. The results of this study by using a number of criteria indicate that LPTK has shown dynamics to strive towards world universities. Yet the dynamics are still small and limited, because faced with a certain number of constraints, namely (1) the lack of academic qualifications of teaching staff come from overseas graduates, as required as one of the criteria towards WCU; (2) improving the quality of lecturers is often hindered by foreign language skills, the elderly, funding, and limited provider institution quality graduate programs; (3) sending lecturers to continue their studies abroad are still hanging from the directorate Higher Education; (4) the submission of budgetary limitations that do not provide the flexibility to call / use a guest lecturer / adjunct lecturer who come from abroad; (5) there are many new courses that achieve accreditation status B / C in the assessment of BAN PT, so they concentrated on improving the status of accreditation of the study programs; (6) the reliance fund / budget delivery of education LPTK against the government (APBN), so the lack of flexibility in allocating funds specifically aimed at supporting the WCU program; (7) the appointment of a lecturer / lecturer in LPTK are insufficient to meet the needs, especially in terms of the angle ratio of the number of faculty and students; and (8) lack of journals in college container itself or else outside an accredited institution of national / international lecturers publish scientific papers.